USING THE METHOD OF INTERACTIVE AND INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Academia Science Repository, 2023)
Fundamental changes in the educational process in our country require accelerating the development of the educational sphere in every educational institution. It is safe to say that pedagogical technologies will become the main source of innovation in education in the coming years. Now, as a result of the development of science, technology and innovative technologies, interest, attention to improving the effectiveness of education, the use of interactive methods (innovative pedagogical and information technologies) in the educational process, is gaining momentum day by day. Training, in which modern technologies are used in the education system, is aimed at independently finding the knowledge acquired by young people, independently studying and analyzing them, evaluating their knowledge, making the right conclusions.